Determinants and Effects on Property Values of Participation in Voluntary Cleanup Programs: The Case of Colorado - Anna Alberini (Fondazione Eni Enrico Mattei (FEEM), 2006)
State Voluntary Cleanup Programs (VCPs) were established starting in the 1990s to encourage the environmental remediation and redevelopment of contaminated properties. These programs typically offer liability relief, subsidies and other regulatory incentives in exchange for site cleanup. This paper asks three questions: First, what type of properties are attracted to voluntary cleanup programs? Second, what is the interaction between these state programs and other incentives for remediation and economic development, such as Enterprise Zone and Brownfield Zone designations? Third, what is the effect of participation in the VCP on property values? We use data from Colorados VCP to answer these questions. We find that most of the properties enrolled in this program were not previously listed on EPAs contaminated site registries, and that most applicants seek to obtain directly a no further action determination without undergoing remediation. The main determinants of participation are the size of the parcel and whether the surrounding land use is primarily residential, while other incentives have little effect. Properties with confirmed contamination sell at a 47% discount relative to comparable uncontaminated parcels, and participation tends to raise the property price, but this latter effect is not statistically significant. Taken together, these findings suggest that the participating properties are those with high development potential, and hint at the possibility that owners or developers may be seeking to obtain a clean bill of health from the State with only minimal or no cleanup efforts. Were these findings confirmed with data from other states, they would raise doubts about the effectiveness of voluntary programs in encouraging remediation and their usefulness in reversing some of the undesired effects of the Superfund legislation.
Keywords: R14; Q58; K32; 330; Brownfields; Contaminated sites; Voluntary cleanup programs; Incentives; Immobilienpreis; Bodenbelastung; Bodensanierung; Hedonischer Preisindex; Colorado (Staat)